2011
DOI: 10.3892/ol.2011.252
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunohistochemical marker, integrin αVβ3, for BOP-induced early lesions in hamster pancreatic ductal carcinogenesis

Abstract: Abstract. N-nitrosobis(2-oxopropyl)amine (BOP)-induced pancreatic ductal carcinomas and early ductal lesions in Syrian hamsters have been reported to show histopathological resemblance to those in humans. Specific protein expression profiles have been found in human carcinomas, but a detailed molecular approach regarding the dissection of BOP-induced pancreatic carcinogenesis has yet to be determined. The present immunohistochemical study of early and advanced hamster lesions focused on five proteins reported … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…This model provides unique characteristics that are similar to a sequence of well-characterized morphologic changes in the human pancreatic duct and frequently shows point mutations in codon 12 of the K-ras gene, in accordance with human findings (23,24). We found that a v b 3 -integrin was overexpressed not only in adenocarcinomas but also in atypical hyperplasia in this hamster model (25). Therefore, this model is useful in the development of imaging probes for the early detection of pancreatic carcinogenesis.…”
supporting
confidence: 56%
“…This model provides unique characteristics that are similar to a sequence of well-characterized morphologic changes in the human pancreatic duct and frequently shows point mutations in codon 12 of the K-ras gene, in accordance with human findings (23,24). We found that a v b 3 -integrin was overexpressed not only in adenocarcinomas but also in atypical hyperplasia in this hamster model (25). Therefore, this model is useful in the development of imaging probes for the early detection of pancreatic carcinogenesis.…”
supporting
confidence: 56%
“…The extrapancreatic common bile duct and ampulla of Vater were ligated before the dye was injected to prevent it from effluxing into the liver and duodenum. 24 Pancreatic ducts were isolated using micro scissors, forceps, and scalpels under a stereomicroscope (Fig.…”
Section: Isolation Of Pancreatic Ducts and Histopathological Classifimentioning
confidence: 99%
“…16,17 Another animal model, hamster pancreatic ductal carcinogenesis induced by N-nitrosobis(2-oxopropyl)amine (BOP), has been extensively studied because of similarities in morphological changes and common genetic alterations, such as KRAS and p16 genes, with humans and the convenience of the carcinogen treatment and handling. 24 On the basis of these genetic, histomorphological, and immunohistochemical profiles, the hamster model was considered to be adequate for investigating molecular profiles, especially in the early lesions of pancreatic carcinogenesis. 23 In our recent study, several proteins, which were previously reported to be up-regulated in human IDCs of the pancreas and involved in cell-to-cell or cell-to-matrix interactions, were similarly confirmed to be expressed not only in IDCs but also in early lesions in hamsters.…”
mentioning
confidence: 99%
“…Preneoplastic and neoplastic ductal lesions in the pancreas were diagnosed as atypical ductal hyperplasia and pancreatic ductal adenocarcinoma, respectively (Pour et al, 1981;Takahashi et al, 2008;Kitahashi et al, 2011;Okamura et al, 2013). Atypical ductal hyperplasias in the pancreas were characterized by proliferation of the duct epithelium with minimal to moderate cellular atypia, with or without mucous metaplasia.…”
Section: Seventeen-week Experimentsmentioning
confidence: 99%